An internet-based self-help intervention for the reduction of consumption of ultra-processed products and increase of physical activity in Mexican university population: study protocol for a randomized controlled trial - González-Cantero, Joel Omar; López-Torres, Leyna Priscila; Alvarado-Avalos, Itzel Refugio; López-Alcaraz, Fátima; Gasca-Suarez, Estefania; Cisneros-Hernández, Adrian Antonio; Valadez, Alexandra; Macías-Espinoza, Fabiola; Dominguez-Rodriguez, Alejandro (Frontiers in Nutrition, 2024)
Introduction The consumption of ultra-processed products has been associated with the etiology of various diseases, mainly metabolic diseases. On the other hand, physical activity acts as a protective factor that helps prevent the appearance of this type of disease. In addition to the physical effects, both the consumption of Ultra-Processed Products (UPPs), and sedentary behaviors have been associated with a significant impact on people's mental health. These problems occur significantly in university students. Online internet interventions are an alternative that has the advantage of reaching a broader sample size and adapting to various problems. Methods. A randomized controlled clinical superiority trial with two independent groups will be developed with 176 participants. Participants in both groups will be evaluated in five moments: 1) pretest, 2) middle of the intervention, 3) post-test, 4) follow-up at three months, and 5) follow-up at 6 months. In the experimental group ("UNISALUD"), participants will receive an intervention composed of 11 sessions with interactive elements such as videos, audio, and infographics created through the User Experience (UX) principles and based on the Health Action Process Approach (HAPA). The participants in the control group will be on the waiting list and will receive treatment 27 days after fulfilling the inclusion criteria. Thus, participants will not receive the treatment immediately. Discussion. The study is expected to establish the feasibility of a self-help internet-based intervention created based on the user experience methodology and the health action process model, leading to a significant decrease and increase in the consumption of UPPs, ultra-healthy products, and physical activity respectively. Conclusion. Internet-based interventions are scarce in Latin America. Due to their potential, this study will provide data about UPPs consumption, physical activity, and mental health of the Mexican population, which will allow to influence the reduction of health-related complications through prevention strategies or measures. Clinical trial registry number: NCT05834842